Effect of Different Bypass Fat Sources on Nutrient Utilization, Blood Parameters and Growth in Male Murrah Buffalo Calves - Len, T.V.; Malla, Bilal A.; Sharma, A.N.; Kumar, Sachin; Tyagi, Nitin; Tyagi, A.K. (Indian Journal of Animal Nutrition, 2018)
Eighteen animals were divided into three groups of 6 animals each in a completely randomized design to study the effect of different rumen protected fat sources on utilization of nutrients, blood parameters and growth in male buffalo calves. All animals were fed with concentrate mixture, green fodder and wheat straw in 50: 40: 10 ratio as per requirements. Prilled fat (PFA) treatment was supplemented with rumen protected palm oil at level of 4% of concentrate mixture on DM basis while soybean fed group (CaSFA) and linseed oil (CaLFA) treatments were supplemented with 4.67% of calcium salt of soyabean oil and linseed oil, respectively. Dietary protected fat sources did not influence the nutrient intake and growth of animals. No significant effect was observed on digestibility of nutrients except that EE and OM digestibility was higher in CaSFA and CaLFA group as compared with PFA group. Polyunsaturated fatty acids (PUFA) added to diet significantly affected (P<0.05) plasma malondialdehyde and insulin like growth factor-1 (IGF-1) level. Mean scrotal circumference improved in buffalo fed CaSFA and CaLFA as compared to PFA. It might be concluded that dietary supplementation of rumen protected fat sources rich in PUFA resulted in the improvement in digestibility of EE and OM. It also increased IGF-1 level and scrotal circumference in male buffalo calves as compared saturated fatty acid rich diet.